EFEK MEDIASI JOB SATISFACTION PADA PENGARUH WORK ENGAGEMENT DAN CAREER MANAGEMENT TERHADAP INTENTION TO STAY PARA TENAGA PENGAJAR DI AKADEMI ATCKR - Kemie, Silvester Sedu (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2019)
This study aims to examine the effects of work engagement and career management on intention to stay for The Teachers at Academy of ATCKR using job stisfaction as an intervening variable. The data were collected using non-probability sampling method, precisely by purposive sampling technique or judgment sampling, on 81 teaching staffs at the ATCKR Academy. The data analysis method used path analysis with SPSS V.23 software program. Path Analysis is used, because in this study there was an intervening variable, namely job satisfaction. The results of the study showed that work engagement and career management had a significant effect on job satisfaction, but had no significant effect on the intention to stay. Work engagement and career management had a significant effect on intention to stay when mediated by job satisfaction. Thus, the mediation carried out by job satisfaction was a perfect mediation.